Effectiveness of the professional who carries out the health education program: perinatal outcomes - Martínez-Galiano JM; Delgado-Rodríguez M (Dove Medical Press, 2014)
Juan Miguel Martínez-Galiano,1–3 Miguel Delgado-Rodríguez2,31Hospital San Juan de la Cruz, Ubeda, 2Department of Health Sciences, University of Jaén, Jaén, 3Biomedical Research Centre Network for Epidemiology and Public Health, Ministry of Health, Institute of Health Carlos III, Madrid, SpainBackground: The purpose of this study was to determine whether a maternal education program conducted by midwives achieves better results in regard to maternal and newborn health than when the program is conducted by other health professionals.Methods: Five hundred and twenty primiparous women attending four (two university) public hospitals in southern Spain in 2011 were recruited to participate in this prospective cohort study. Data on sociodemographic and obstetric variables and characteristics of newborns were collected by interviews and from clinical charts. Crude and logistic regression adjusted odds ratios (aORs) and confidence intervals (CIs) were estimated.Results: A midwife was in charge of education for 75.4% of the 354 women who attended maternal education programs. Midwife-conducted programs had significantly more women attending more than three sessions than the programs conducted by other health professionals (aOR 2.85, 95% CI 1.60–5.11). Midwives achieved more active participation from mothers during delivery (aOR 1.96, 95% CI 1.15–3.33), more early skin-to-skin contact between the mother and newborn (aOR 1.79, 95% CI 1.01–3.23), more early breastfeeding (aOR 2.08, 95% CI 1.18–3.70), and fewer newborns with low birth weight (aOR 0.14, 95% CI 0.03–0.65) compared with other health professionals.Conclusion: Midwives achieve better results than other health professionals in regard to the health of the mother and her newborn when they are in charge of the maternal education program.Keywords: maternal education program, midwifery, childbirth, other health professionals